Factors Influencing Patients' Satisfaction with Meals Served at Hospitals in Malaysia - Siti Nur Batrisyia Marzuki; Nur Safiyyah Zainal; Siti Noraisah Dolah Abdullah; Hawaliana Selamat; Siti Nor Fadillah Ahmad Shariff (Information Management and Business Review, 2025)
Hospitals play a vital role in restoring patients' health, and the quality of food served can significantly contribute to the recovery process. The food's taste, appearance, and freshness are key factors that can enhance patient satisfaction and, in turn, build trust, improving the hospital's overall performance. Given the many meals served to patients, hospital food service is a critical component of hospital management, with the potential for growth and improvement in service delivery. This research will examine the factors influencing food quality, including taste, appearance, and freshness, and explore how these elements impact patient satisfaction. The findings aim to help hospitals identify areas for improvement and enhance their food service operations.